General FEM model of prestressing tendons - Antoniak, Daniel; Konderla, Piotr (Computer Assisted Methods in Engineering and Science, 2023)
The paper presents a general numerical model for the analysis of prestressed concrete with the application to beam, thin shell and volume type of prestressed structures. Discrete, embedded approach is used to model curved, bonded or unbonded tendons. Also a partial bond may be introduced by the friction between the tendon and the surrounding body. In the finite element model, two types of elements are obtained. One is a typical finite element for the kind of structure modeled, and the other is an embedded, three noded, subparametric tendon element. Equations of the finite element method have been obtained from the incremental form of the principle of virtual work providing geometrical linearity and possibility of nonlinear physical relations. Numerical examples illustrate application to modeling of beam, thin shell and volume type of prestressed structures as well as the impact of the friction on the axial force distribution in prestressing tendon.